PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TEAMS GAMES TOURNAMENT (TGT) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS V SD N 028 SERUSA KECAMATAN BANGKO KABUPATEN ROKAN HILIR - Rahman, Yeni; Noviana, Eddy; ', Zufriady (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The purpose of this study was to determine whether the application of the Model Cooperative Learning Teams Games Tournament (TGT) can improve learning outcomes fifth grade science students SD N 028 serusa. Forms of this research is is a Class Action Research (PTK) with the research subjects were fifth grade students who berjumalah 20 people. The basic problem in this research is the low student learning outcomes that are marked are still many students who are under the KKM. Data collection techniques used is observation and tests. Results concluded that learning science by Model Cooperative Learning Teams Games Tournament (TGT) may enhance the activity of teachers, student activity and learning outcomes IPA. In the first cycle of meeting 1 total score of teacher activity that is 30%, then increased at a second meeting with the activity score was 60% in enough categories. At the first meeting of the second cycle the average amount of activity obtained namely 65%, then increased at a second meeting with an average activity was 90% in both categories once. The average percentage of student activity in the first cycle of meeting 1 percentage amount obtained namely 60%, then increased at a second meeting with the student activity 80%. At the first meeting of the second cycle of activity obtained percentage amount that is 85% and then increased in the second meeting with the percentage of activity was 90%. The average student learning outcomes in the first cycle of meetings 1 is 66.75%, in the first cycle of the second meeting of the average value of 75.75% and an increase of 9%. The average results of studying the second cycle of the first meeting with the average value of 75.25%, the second cycle of the second meeting of the average value of the results of learning to be 82.5% with an increase of 7.25%Keywords: Cooperative Learning Model Teams Games Tournament (TGT), learning outcomes IPA.